Significance of Fundamental Metrology of 3D-Printed Parts for Engineering Design: Dimensional Accuracy - Gerald Sanqui Robles; Michaela Tayag Espino; Ray Noel Medina Delda; John Ryan Cortez Dizon (Universitas PGRI Semarang, 2022)
This paper discusses some basic metrology considerations when 3D printing. The importance of ensuring correct measurements is highlighted especially for practical applications. The last part of the paper presents sample dimensional measurements of 3D-printed parts with varying sizes, infill density and layer thickness. Different cube sizes of 10 mm3, 15 mm3, and 20 mm3 has been produced using a commercially-available 3D printer. Acrylonitrile butadiene styrene (ABS) has been used for the experiments. Important observations and insights are presented.